Characterization of SIBLING Proteins in the Mineralized Tissues - Sandeep Dab; Nancy Abdelhay; Carlos Alberto Figueredo; Seema Ganatra; Monica Prasad Gibson (MDPI AG, 2022)
The SIBLING proteins are a family of non-collagenous proteins (NCPs) previously thought to be expressed only in dentin but have been demonstrated in other mineralized and non-mineralized tissues. They are believed to play vital roles in both osteogenesis and dentinogenesis. Since they are tightly regulated lifelong processes and involve a peak of mineralization, three different age groups were investigated. Fifteen wild-type (WT) mice were euthanized at ages 1, 3, and 6 months. Hematoxylin and eosin staining (H&E) was performed to localize various microscopic structures in the mice mandibles and tibias. The immunostaining pattern was compared using antibodies for dentin sialoprotein (DSP), dentin matrix protein 1 (DMP1), bone sialoprotein (BSP), and osteopontin (OPN). Immunostaining of DSP in tibia showed its most noticeable staining in the 3-month age group. DSP was expressed in alveolar bone, cellular cementum, and PDL. A similar expression of DMP1 was seen in the tibia and dentin. BSP was most noticeably detected in the tibia and acellular cementum. OPN was mainly expressed in the bone. A lower level of OPN was observed at all age groups in the teeth. The immunostaining intensity was the least detected for all proteins in the 6-month tibia sample. The expression patterns of the four SIBLING proteins showed variations in their staining intensity and temporospatial patterning concordant with skeletal and dental maturity. These findings suggest some role in this tightly regulated mineralization process.